Upaya meningkatkan kemampuan komunikasi matematis siswa melalui penerapan model pembelajaran discovery learning di kelas VIII SMPN 23 Medan (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This study aims to improve students' mathematical communication skills using the Discovery Learning model in class VIII of SMP Negeri 23 Medan TP. 2018/2019. This study is a Classroom Action Research which was carried out in 2 cycles, where each of the first and second cycles consist of 2 meetings. The subjects in this study were students of class VIII-G in SMP Negeri 23 Medan. The object of this research is learning activities using Discovery Learning model to improve students' mathematical communication skills. The research data was collected through tests, observation and interviews. The results of data analysis on the second mathematical communication skills’ test showed that there were 31 students (86.11%) who had reached the learning completeness criteria, while 5 students (13.89%) had not reached it yet. The results also showed that students experienced an increase in the class average score, where the class average score in the first cycle was 70.22, increasing to 80.47 in the second cycle. In addition, the level of classical learning completeness of students also increased, with the level of classical learning completeness of students in the first cycle of 66.67% increasing to 86.11% in the second cycle. From the results of the data analysis of those two cycles, it can be seen that the criteria for students' mathematical communication skills have reached the target and have increased through the application of the Discovery Learning model. Thus it can be concluded that the Discovery Learning model can improve students' mathematical communication skills in class VIII-G of SMP Negeri 23 Medan.
Keywords: classroom action research; discovery learning; students' mathematical communication skills